Neighborhood Sociodemographic Effects on the Associations Between Long-term PM2.5 Exposure and Cardiovascular Outcomes and Diabetes Mellitus. Issue 1 (February 2019) - Weaver, Anne M.; McGuinn, Laura; Neas, Lucas; Mirowsky, Jaime; Devlin, Robert B.; Dhingra, Radhika; Ward-Caviness, Cavin; Cascio, Wayne E.; Kraus, William E.; Hauser, Elizabeth R.; Di, Qian; Schwartz, Joel; et al.
Abstract : Background: Exposure to PM2.5 air pollution and neighborhood-level sociodemographic characteristics are associated with cardiovascular disease and possibly diabetes mellitus. However, the joint effect of sociodemographics and PM2.5 on these outcomes is uncertain. Methods: We examined whether clusters of sociodemographic characteristics modified effects of long-term PM2.5 exposure on coronary artery disease (CAD), myocardial infarction (MI), hypertension, and diabetes mellitus. We used medical records data from 2, 192 cardiac catheterization patients residing in North Carolina and assigned to one of six previously determined clusters. For each participant, we estimated annual PM2.5 exposure at their primary residence using a hybrid model with a 1 km 2 resolution. We used logistic regression models adjusted for age, sex, body mass index, and smoking status to assess cluster-specific associations with PM2.5 and to determine if there were interactions between cluster and PM2.5 on outcomes. Results: Compared with cluster 3 (OR = 0.93, 95% CI = 0.82, 1.07; urban, low proportion of black individuals and high socioeconomic status), we observed greater associations between PM2.5 and hypertension in clusters 1 (OR = 1.22, 95% CI = 0.99, 1.50, P int 0.03) and 2 (OR = 1.64, 95% CI = 1.16–2.32, P int 0.003), which were urban, high proportion of black individuals, and low socioeconomic status. PM2.5 was associated with MI (OR = 1.29, 95% CI = 1.16, 1.42) but not diabetes mellitus, regardless of cluster and was associated with CAD in cluster 3 (OR = 1.15, 95% CI = 1.00, 1.31) and overall (OR = 1.07, 95% CI = 0.98, 1.17). Conclusion: Areas of relative disadvantage have a stronger association between PM2.5 and hypertension compared with areas of relative advantage. Abstract : Supplemental Digital Content is available in the text.